Defense Peptides From the α-Hairpinin Family Are Components of Plant Innate Immunity - Slavokhotova, Anna A.; Rogozhin, Eugene A. (Frontiers in Plant Science, 2020)
Plant immunity represents a sophisticated system, including both basal and inducible mechanisms, to prevent pathogen infection. Antimicrobial peptides are among the innate immunity components playing a key role in effective and rapid response against various pathogens. This review is devoted to a small family of defense peptides called α-hairpinins. The general characters of the family, as well as the individual features of each member, including biological activities, structures of precursor proteins, and spatial structures, are described. Possible applications of α-hairpinin peptides in drug design are discussed.